HUBUNGAN PEMBELAJARAN FIQH THAHARAH DALAM MENJAGA KEBERSIHAN DI SMP PERMATA INSANI ISLAMIC SCHOOL TANGERANG - Maemunah - Maemunah; Siti Aan Anwariyah; Uus Syaripudin (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2022)
This study aimed to determine the relationship between Fiqh (thaharah) learning and Awareness of Maintaining Cleanliness in Schools for Grade VII Students at SMP Permata Insani Islamic School Tangerang. This research is field research with a correlational quantitative research design. This research uses correlational research or relationship search because it is carried out to determine the strata of the relationship between two variables without making changes, additions, or manipulations to existing data. The results of the research that have been analyzed in the formulation of the problem are that there is found a positive correlation between learning fiqh thaharah with awareness of maintaining cleanliness in schools in class VII students at SMP Permata Insani Islamic School Tangerang, where the value of r (Pearson Correlation) is 0.454 there is a medium category and based on the table of interpretation of the coefficient of the value of r.